The Development Of Animation Video-Based Learning Media On The Polyhedron Material Assited By Powtoon Software - Nanda Ayu Dwi (UMSU, 2022)
This research aims to; 1) Knowing the feasibility of learning mathematics media on flat-sided building materials based on animated videos on flat-sided space-building materials; 2) Knowing students' responses to the use of mathematics learning media in side-building materials based on animated videos assisted by Powtoon software, 3) Knowing students' responses to the use of mathematical mathematics learning media in side-space building materials based on animated videos assisted by Powtoon software. This study uses the Research and Development (R D) research method according to Borg and Gall. The research subjects involved were one media expert, one material expert, mathematics study teacher, and seventh grade students at MTs Al-Washliyah Tebing Tinggi. The experts gave an assessment of the feasibility of the product developed by the researcher, while the students and teachers responded about the attractiveness of the product developed. The results of this study are 1) The product produced is categorized as very feasible based on validation from material experts with a presentation of 92% and media experts with a presentation of 82%. 2) Powtoon is very interesting to be used as teaching material based on the teacher's assessment getting a presentation of 81%, and student responses to field trials getting a percentage of 89%.